Bramble Energy shows 1 kW Big Kahuna unit. Issue 3 (March 2020) - Unknown
Abstract : UK-based Bramble Energy has unveiled a 1 kW hydrogen fuel cell system, internally referred to as the K1000 or 'Big Kahuna', the first prototype of which is now undergoing initial laboratory testing protocols and iterations.